2011
DOI: 10.1523/jneurosci.2587-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Sense of Memory Strength and the Objective Amount of Information Accurately Remembered Are Related to Distinct Neural Correlates at Encoding

Abstract: Although commonly used, the term memory strength is not well defined in humans. Besides durability, it has been conceptualized by retrieval characteristics, such as subjective confidence associated with retrieval, or objectively, by the amount of information accurately retrieved. Behaviorally, these measures are not necessarily correlated, indicating that distinct neural processes may underlie them. Thus, we aimed at disentangling neural activity at encoding associated with either a subsequent subjective sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 46 publications
5
60
3
Order By: Relevance
“…First, this paradigm has been shown to assess memory for the gist of an episode (Adolphs et al, 2001(Adolphs et al, , 2005Qin et al, 2011). Thus, it allowed us to more closely examine the hypothesis of how acute stress leads to a shift of mnemonic processing toward extracting central thematic information, or gist.…”
Section: Encoding Task and Memory Testmentioning
confidence: 99%
“…First, this paradigm has been shown to assess memory for the gist of an episode (Adolphs et al, 2001(Adolphs et al, , 2005Qin et al, 2011). Thus, it allowed us to more closely examine the hypothesis of how acute stress leads to a shift of mnemonic processing toward extracting central thematic information, or gist.…”
Section: Encoding Task and Memory Testmentioning
confidence: 99%
“…However, whereas the mnemonic metacognitive network found in the Baird et al (2013) study included right parietal clusters, indications of parietal involvement in episodic retrieval success are more generally associated with left hemispheric activations (Wagner et al, 2005). Similarly, an investigation into the subjective sense of memory strength found that confidence in relating the gist of a scene correlated with left rather than right hemisphere lateral parietal activations (Qin et al, 2011). The significance of this discrepancy regarding laterality is unclear.…”
mentioning
confidence: 99%
“…in the hippocampus as opposed to smaller percentage in cortical areas [17]. This could also relate to the fMRI data results revealing that activation in left ventral lateral prefrontal cortex and temporoparietal junction predicted subsequent confidence ratings and in contrast, parahippocampal and hippocampal activity predicted the number of details remembered [13].…”
Section: Resultsmentioning
confidence: 89%
“…Unfortunately, literature is not very clear on how to measure aspects of working memory [13] such as sustainability, item retention, delay interval and the decay of memory traces etc. Here we therefore measure PNG quality in two ways: 1. by their strength, and by 2. their duration.…”
Section: Methodsmentioning
confidence: 99%